Knowledge, attitude and practice of family planning among reproductive age group women of urban and rural areas of Gadag: a comparison study - Iti, Jannatbi; Mudaraddi, Roshan (International Journal Of Community Medicine And Public Health, 2020)
Background: India is the second most populous country in the world 1.311 million (2015). With only 2.4% of the world land area India is supporting 17.5% of the world population. The rampant population growth has been viewed as the greatest obstacle to the economic and social advancement. Reproductive choice is one of the most fundamental rights of a couple. Empowering a woman to control her fertility allows her to complete her education or employment aspirations. Aim and objective of the study was to know the distribution of socio-demographic factors which influence KAP about FP methods among eligible reproductive age group women. Methods: A community based cross sectional study was done from 27 March 2017 to 20 April 2017 in rural and urban areas of Gadag Taluk in women of eligible reproductive age group with a sample size of 560. Results: 25.4% of the women are in the age group of 28-32 years. Majority of the women belonged to Hindu (87.5%) and 11.1% Muslims. Highest proportion of women have completed middle and high school which amounts to 42.3%. and 17.7% were illiterates. 43.6% of the respondents married at the age of 20-24 years, 48.2% of the women were homemakers, 3.6% were professionals and 1.8% were semi-professionals and 23.2% were unskilled. Conclusions: Family planning is the most effective measure to bring control on the population. Knowing the socio-demographic factors which influence the adoption of family planning methods is of utmost importance to plan for birth control and spacing children especially for the policy makers.